2008
DOI: 10.1142/s0219498808002631
|View full text |Cite
|
Sign up to set email alerts
|

An Affirmative Answer to a Question on Noetherian Rings

Abstract: It is shown that a ring R is right noetherian if and only if every cyclic right R-module is a direct sum of a projective module and a module Q, where Q is either injective or noetherian. This provides an affirmative answer to a question raised by P. F. Smith.and Osofsky-Smith [20], respectively): Theorem A. A ring R is right noetherian if and only if every cyclic right R-module is a direct sum of a projective module and a noetherian module.Theorem B. A ring R is right noetherian if every cyclic right R-module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Since then, there has been continuous work on finding properties on classes of modules that guarantee the ring to be right noetherian (or some other finiteness condition). For instance, if each cyclic right module is: an injective module or a projective module [5], a direct sum of an injective module and a projective module [12,14], or a direct sum of a projective module and a module Q, where Q is either injective or noetherian [6], then the ring is right noetherian. It is also known that if every finitely generated right module is CS, then the ring is right noetherian [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there has been continuous work on finding properties on classes of modules that guarantee the ring to be right noetherian (or some other finiteness condition). For instance, if each cyclic right module is: an injective module or a projective module [5], a direct sum of an injective module and a projective module [12,14], or a direct sum of a projective module and a module Q, where Q is either injective or noetherian [6], then the ring is right noetherian. It is also known that if every finitely generated right module is CS, then the ring is right noetherian [7].…”
Section: Introductionmentioning
confidence: 99%
“…In [24], it was shown that a ring R is right Noetherian if (and only if) every cyclic right R-module is a direct sum of a projective module and a module Q , where Q is either injective or Noetherian. But here, with our condition (℘), we cannot obtain the same result.…”
Section: When Are Wv-rings Noetherian?mentioning
confidence: 99%